Fiscal Decentralization and Farmer Empowerment in Indonesia-Timor Leste Border: A Case Study of Village Fund - Sipayung, Boanerges Putra; Joka, Umbu; Maulana, Achmad Subchiandi; Onuigbo, Dennis Mark (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Farmers in the border areas often face challenges due to a lack of facilities and sufficient infrastructure. As a nation that shares borders with several countries, the Indonesian government aims to facilitate economic growth in these areas. One viable approach to achieve this objective is through the effective allocation of village funds. Therefore, this study aims to analyze the factors influencing the empowerment of farmers in the Indonesia-Timor Leste border using village funds. Data were collected using a survey method from 325 household heads, who served as respondents. The collected data were analyzed using the Structure Equation Model-Partial Least Square (SEM-PLS). The results showed that human, social and physical capital owned by farmers on the Indonesia-Timor Leste border had an indirect effect on the strength of empowerment programs funded through village funds. This indicated that apart from implementing policies, the community must also be involved in the planning and implementation of various programs. Furthermore, the central or regional government must play an active role during the designing stages as well as involve farmers and experts in the empowerment process in the Indonesia-Timor Leste border areas.